1974
DOI: 10.1002/ps.2780050110
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of chlorfenvinphos and phorate from soil by carrots as influenced by mode of application and cultivar

Abstract: Granular formulations of chlorfenvinphos and phorate were applied to sandyloam soil at 2 kg a.i./ha either broadcast and incorporated to 2.5 cm, broadcast and incorporated at 10 cm or by the bow-wave method along the carrot rows. Depth of incorporation did not influence the rates of residue decline in the soil. Bow-wave applications produced the highest residues in root and foliage and also reduced the rate of oxidation of phorate. 30 weeks after sowing the carrots, all treatments gave the highest residue conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Residues in both studies were generally less than 0.05 ppm except in carrots and parsnips where they approached the 0.10ppm level. Suett (1974) found that the rate and amount of insecticide uptake by carrots are influenced by the rate and mode of insecticide application and by the carrot cultivar. The depth of incorporation of the insecticide had little bearing on the rate of decline ofresidues in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Residues in both studies were generally less than 0.05 ppm except in carrots and parsnips where they approached the 0.10ppm level. Suett (1974) found that the rate and amount of insecticide uptake by carrots are influenced by the rate and mode of insecticide application and by the carrot cultivar. The depth of incorporation of the insecticide had little bearing on the rate of decline ofresidues in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…It is volatile and volatilization is probably a major factor in its dissipation from soil (Getzin and Chapman 1960; Harris and Lichtenstein 1961; Getzin and Shanks 1970). In addition it is oxidized in soil to the sulfoxide and sulfone (Getzin and Chapman 1960;Parker and Dewey 1965; Dewey and Parker 1965; Bache and Lisk 1966; Getzin and Shanks 1970;Menzer et al 1970; Suett 1971Suett , 1974Suett , 1975; Schulz et a l . 1973; Lichtenstein et a l .…”
mentioning
confidence: 99%
“…the sulfoxide can be reduced by microbial action to phorate, particularly in flooded soil (Getzin and Shanks 1970;Walter-Echols and Lichtenstein 1977). The mobility of phorate in soil is limited, but the more water soluble sulfoxide and sulfone move more readily (Getzin and Suett 1971Suett , 1975; Schulz et al 1973; Lichtenstein et al 1974). Persistence studies generally indicate that phorate degrades relatively quickly in soil but that the sulfoxide and sulfone are more persistent.…”
mentioning
confidence: 99%
See 2 more Smart Citations